State versus market : have Asian currency crises affected the reform debate? - Stiglitz, Joseph E.; Bangladesh Economic Association (Dhaka : Published for Bangladesh Economic Association [by] University Press, 1999)
Transcript of a lecture organized by Bangladesh Economic Association in Dhaka on March 14, 1999.
Includes bibliographical references (pages [51]-52) and index.
ESS
Complimentary copy from Professor Dr. Nasreen Khundker.
Donated by Akbar Ali Khan
Keywords: Economic policy; Asia -- Economic policy